Identify Water Treatment Plant Capability in Removing Microplastic : Lab Scale Simulation and Direct Sampling - Wa Ode Sitti Warsita Mahapati; Emenda Sembiring; Syarif Hidayat (Journal of Multidisciplinary Academic, 2022)
The challenges of Drinking Water Treatment Plants (DWTP) are increasing due to the presence of new types of pollutants that can contaminate raw water and increase the processing load on the installation. One of the pollutants that is currently being discussed a lot is plastic particles measuring < 5 mm which are called microplastics. Based on these factual conditions, it is also important to identify the generation of microplastics at the raw water treatment plant in Bandung-Indonesia. In this study, laboratory-scale water treatment simulations and sampling at two drinking water treatment plants in Bandung City were carried out using the grab sampling method to identify their generation in the laboratory. The results showed that microplastics were still found in all processing units, this was in line with laboratory-scale processing which showed that the processing still left residue at the final stage of the experiment. So, it can be concluded that further research is needed to optimize the performance of conventional water treatment units in removing microplastics and the mechanism that can be applied to prevent the spread of microplastics into water bodies.